2005
DOI: 10.1186/1471-2407-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Phase III trial of postoperative cisplatin, interferon alpha-2b, and 5-FU combined with external radiation treatment versus 5-FU alone for patients with resected pancreatic adenocarcinoma – CapRI: study protocol [ISRCTN62866759]

Abstract: After surgical intervention with curative intention in specialised centres the five-year survival of patients with carcinoma of the exocrine pancreas is only 15%. The ESPAC-1 trial showed an increased five-year survival of 21% achieved with adjuvant chemotherapy. Investigators from the Virginia Mason Clinic have reported a 5-year survival rate of 55% in a phase II trial evaluating adjuvant chemotherapy, immunotherapy and external-beam radiation. Design:The CapRI study is an open, controlled, prospective, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 26 publications
0
37
0
5
Order By: Relevance
“…2,22 However, the mechanism by which IFN-a in pancreatic carcinoma mediates its beneficial effect remained unclear. It is well known that the activity of NK cells is regulated by various cytokines, among them IFN-a, 23 and recent studies have implicated IFN-a in the induction of NKG2DL expression, especially on dendritic cells leading to subsequent activation of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,22 However, the mechanism by which IFN-a in pancreatic carcinoma mediates its beneficial effect remained unclear. It is well known that the activity of NK cells is regulated by various cytokines, among them IFN-a, 23 and recent studies have implicated IFN-a in the induction of NKG2DL expression, especially on dendritic cells leading to subsequent activation of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A shows the KaplanMeier survival curve of this patient cohort. Seven patients received first-line adjuvant chemotherapy with gemcitabine, two patients were included into the CapRI study (for protocol, see reference Knaebel et al, 2005), one patient received gemcitabine/capecitabine and eight patients received no chemotherapy. Analysis of seven patients treated with first-line gemcitabine revealed a time to relapse of 193 days, as judged by time from initiation of chemotherapy until radiologically detected recurrence of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Although the clinical efficacy of IFN-· for pancreatic cancer has been already reported, most of these studies have reported the effect of IFN-·-based combination therapy with other drugs including 5-fluorouracil, cisplatin retinoic acid, or leucovorin (11)(12)(13)(14)(15)(16). Considering that GEM is the golden standard chemotherapeutic agent today, in order to develop more effective combination chemotherapy for pancreatic cancer, we thought it was important to evaluate the antitumor effect of the combination therapy of IFNs and GEM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our group has reported the antitumor effect of IFN-· and 5-fluorouracil on hepatocellular carcinoma (HCC) (8)(9)(10), while others have also documented the clinical effect of IFN-· in pancreatic cancer (11)(12)(13)(14)(15). In this regard, a 5-year survival of 55% following IFN-·-based adjuvant chemoradiotherapy for patients with resectable pancreatic cancer it has been reported (16).…”
Section: Introductionmentioning
confidence: 98%